2019
DOI: 10.1016/j.apmr.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Gait- and Posture-Related Factors Associated With Changes in Hip Pain and Physical Function in Patients With Secondary Hip Osteoarthritis: A Prospective Cohort Study

Abstract: Title: Gait-and posture-related factors associated with changes in hip pain and physical function in patients with secondary hip osteoarthritis: a prospective cohort study ABSTRACT Objective: To identify gait-and posture-related factors associated with changes in hip pain and physical function in patients with hip osteoarthritis (OA). Design: Prospective cohort study Setting: Clinical biomechanics laboratory of a university Participants: Consecutive sample of 30 female patients with mild-to-moderate secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Conversely, Zeni et al [29] have confirmed that there were no gait parameters, including hip moment, associated with hip pain. Moreover, previous prospective cohort studies have shown that the HAM impulse is associated with radiographical (i.e., structural) hip OA progression but not with worsening of hip pain [2,31]. The relationship between hip pain and gait biomechanics may be modified by various factors such as the condition of joint structures and difference in compensatory strategies for gait using parts other than the hip joint such as the trunk; therefore, hip pain might not be directly related to the HAM impulse.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Zeni et al [29] have confirmed that there were no gait parameters, including hip moment, associated with hip pain. Moreover, previous prospective cohort studies have shown that the HAM impulse is associated with radiographical (i.e., structural) hip OA progression but not with worsening of hip pain [2,31]. The relationship between hip pain and gait biomechanics may be modified by various factors such as the condition of joint structures and difference in compensatory strategies for gait using parts other than the hip joint such as the trunk; therefore, hip pain might not be directly related to the HAM impulse.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between worse and more abnormal gait patterns during a walking test and pain after daily walking was partially explained in some previous studies that suggested that abnormal walking patterns exacerbated joint pain. In their 12-month prospective study, Tateuchi et al reported that limited hip extension and limited external rotation angles during gait were associated with worsening hip pain in patients with hip OA [ 24 ]. In a prospective study of patients with knee OA, a varus thrust of the knee during gait, which is associated with a knee adduction moment, was related to worsening knee pain [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the strength of that study is that the kinematics of the entire limb was considered, the computation obscures the contribution of each of the joints to the gait deviation. Moreover, Tateuchi et al [ 46 ] showed that limited hip extension during gait is one of the factors that was related to a deterioration in physical function in patients with hip OA, suggesting that deviations from kinematics in healthy persons may not only reflect the functional status of patients but are also valuable for predicting outcome.…”
Section: Discussionmentioning
confidence: 99%